Direction and Export Performance of Coffee in India - Ahmadzai, Abdul Baqi; Sidana, Baljinder Kaur; Guleria, Amit (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted in the Department of Economics and Sociology, College of Basic Sciences and Humanities, Punjab Agricultural University, Punjab, India to examine growth performance and share of coffee in agricultural export from 2000-01 to 2016–17. The data on quantity of coffee exports from 2005-06 to 2016-17 were collected and used to examine the direction of trade and changing pattern of coffee exports with the use of first order Markov chain analysis. The top six major destinations in each type of coffee were selected for the analysis. The share of coffee in agricultural export earnings was nearly 4% in 2000-01 and decreased to 2% in 2016–17 which is a matter of great concern. The results of Markov Chain Analysis revealed that the major destinations for Indian coffee were Italy, Germany, Belgium, USA, Turkey and Slovenia. Kuwait was the most stable destination for plantation coffee exports, while in case of Arabica cherry Belgium, for Robusta parchment Italy, Germany and Spain for Robusta cherry and for Instant coffee Turkey and Russian federation were the most stable destinations. The climatic events and supply shocks remain the real threat to the development of a balanced market and sustainable conditions for the Indian coffee economy. The Government of India is expected to announce an interest subsidy scheme for exporters in order to boost coffee exports and explore new markets.